(untitled) (Update Dental College Journal, 2023)
Background: The term "Class II malocclusion" encompasses a range of dental and skeletal characteristics, making precise diagnosis and treatment planning challenging. This study aimed to examine 32 Bangladeshi patients with Class II malocclusion to evaluate maxillary and mandibular skeletal positions using cephalometric measurements commonly used in clinical practice. Methods: Study casts and lateral cephalograms of 32 patients (17 females and 15 males) with Class II malocclusion were analyzed. Inclusion criteria comprised Class II molar relationship, the absence of craniofacial deformities, and no previous orthodontic treatment. Cephalometric measurements included SNA, SNB, and ANB angles, and data were analyzed using SPSS software. Results: Among the patients, 53% exhibited maxillary skeletal protrusion, 43% had mandibular retrusion, and only 3.1% presented both maxillary protrusion and mandibular retrusion. Surprisingly, 31.2% showed maxillary skeletal retrusion, and 28.1% exhibited mandibular protrusion, highlighting the significant variation in skeletal patterns within this cohort. Conclusion: Our findings emphasize the diverse skeletal patterns present among Bangladeshi patients with Class II malocclusion. The implications of these variations for treatment planning are substantial, as the treatment approach may differ depending on the underlying skeletal pattern. Given this diversity, individualized assessment and tailored treatment strategies are essential to achieve optimal outcomes. While this study has provided valuable insights, future research with larger and more diverse samples is warranted to further explore these complex relationships. Update Dent. Coll. j: 2023; 13(2): 34-37